Recent advancements in additively manufactured hip implant design using topology optimization technique - Abdulla All Noman; Mohd Shamil Shaari; Hassan Mehboob; Abdul Hadi Azman (Results in Engineering)
The recent advancement of additive manufacturing (AM) offers many benefits for the medical sector, which is revolutionizing modern bone repair surgery for patients, including those with damaged hip joints. Consequently, AM enables the fabrication of hip replacements made of alloys like titanium, cobalt-chromium, stainless steel, and their alloys. Porous additive-manufactured hip implants possess various advantages, including patient-specific implant design, reduced production cost, mass reduction, and a longer implant life by alleviating stress shielding. Mass and stress shielding reduction of the implants can be achieved through topology optimization techniques incorporating cellular structures. Therefore, porous implant design, topology optimization, and additive manufacturing can merge to improve patient health and medical advancement. Hence, by integrating these three elements, this review represents the recent advancements in the topology optimization of hip implants using the AM technique for designing and fabricating porous hip implants.